Data protection challenges for virtual reality applications. Issue 1 (June 2018) - Henriksson, Emil Albihn
Abstract : Virtual reality technologies necessitate the collection and processing of more – and more intimate – personal data than other media. This gives rise to some particular considerations under data protection regulations and not least the EU General Data Protection Regulation. The aim of this article is to explore these characteristics particular to VR and to identify some of the issues that these might give rise to under the GDPR.